Challenge and Recommendation of Inclusive Education in The Juvenile Prison at Juvenile Rehabilitation Center (LPKA) Class II Yogyakarta - Najah, Adlin Fauzia; Kristaningtyas, Nathania Augustine; Arsalan, Rafi Naufal; Lubis, Salman Hafiz Ar-ramli (Ridwan Institute, 2025)
LPKA Class II Yogyakarta, which is responsible for rehabilitating and educating children in conflict with the law, faces significant challenges in providing inclusive education. This study identifies these challenges and provides recommendations to improve educational outcomes. Utilizing a qualitative approach, the research involved in-depth interviews and Focus Group Discussions (FGD) with 15 respondents and experts. Informed consent was obtained from all participants and data were analyzed using descriptive techniques to provide a comprehensive understanding of the issue. Challenges include internal factors like low motivation, psychological issues, and the desire to work, as well as external factors such as a lack of inclusive schools, unsystematic curricula, and inadequate resources. Financial constraints and limited funding exacerbate these issues. Recommendations include collaboration among stakeholders, implementation of individualized mentoring systems, conducting comprehensive needs assessments, fostering a supportive environment, and engaging in non-profit partnerships, all of which can enhance educational outcomes, reduce recidivism, and facilitate better societal reintegration.